Suicide in Turkey: its changes and regional differences - Yakar, Mustafa; Temurçin, Kadir; Kervankiran, Ismail (Bulletin of Geography. Socio-economic Series, 2017)
The temporal dimensions and tendencies, including some characteristic features of suicide in Turkey during the social transformation process, are the subject of this study with a focus on the provinces and differentiation on a regional scale. The number of suicides in Turkey and the characteristic features of those committing suicide during the years 1974-2013 have been collected in the ’Suicide Statistics’ yearbook within this context. Both the suicide numbers as well as the crude suicide rates in Turkey have increased from the last quarter of the 20th century to the beginning of the 21st century. As a matter of fact the number of suicides which was 788 in 1975 increased at a rate of 304.7% to become 3189 in 2013. The crude suicide rate per 100,000 population increased from 1.95 in 1975 to 1.69 in 1980, to 2.42 in 1990, to 2.67 in 2000 and increased to 4.19 in 2013. Although crude suicide rates are smaller than those in most European countries, the fact that there is a rapidly increasing trend indicates that it has started to become a significant public health problem.